Use the elimination method to solve:
6a  b = 3 b + 4a = 17
First, rearrange the equations to line up the a’s, b’s, and the constant terms.
6a  b = 3 b + 4a = 17 6a  b = 3 {first original equation} 4a + b = 17 {rearranged second original equation} —————— 10a = 20 {added the two equations together} a = 2 {divided each side by 10} Substitute 2, in for a, into one of the two equations. b + 4a = 17 {second original equation} b + 4(2) = 17 {substituted 2, in for a, into second original equation} b + 8 = 17 {multiplied 4 by 2} b = 9 {subtracted 8 from each side} a = 2 and b = 9 Ask Algebra House
0 Comments
Your comment will be posted after it is approved.
Leave a Reply. 
Latest Videos
Archives
May 2024
